The cost of COVID-19 vaccine delivery in Bangladesh - Afroja Yesmin; Flavia Moi; Tarek Hossain; Rachel A. Archer; Monjurul Islam; Laura Boonstoppel (Taylor & Francis Group, 2024)
COVID-19 vaccination has been instrumental in fighting the pandemic, but evidence on the actual costs associated with delivering these vaccines in resource-constrained settings has been limited. We estimated the cost of delivering COVID-19 vaccines in Bangladesh through five delivery strategies in 2021 and 2022, including Ministry of Health (MOH) hospitals, non-MOH government hospitals, outreach at Expanded Program on Immunization (EPI) centers, mass campaigns, and schools. This was a bottom-up costing study, estimating costs from a payer and beneficiary perspective. We also mapped the funding flows for COVID-19 vaccination activities and analyzed programmatic and financial challenges. The economic cost incurred by the health system to deliver COVID-19 vaccines was $1.05 per dose, excluding vaccine costs. This was made up of a financial cost of $0.29 per dose and an opportunity cost of $0.75 per dose. School-based delivery incurred the lowest financial cost of $0.27, while outreach at EPI centers incurred the highest at $0.44 per dose. The low financial cost per dose is attributed to the high daily volumes delivered at sampled sites, minimal additional resources provided to sites to implement the COVID-19 vaccination program, and a reliance on the existing workforce. Beneficiaries spent an average of $1.63 to receive a single dose of COVID-19 vaccination at fixed sites, with transport representing the largest cost driver ($0.75 per dose). The economic cost to receive one dose of the COVID-19 vaccine was $4.78. Findings can support the Government of Bangladesh to make efficient and equitable resource allocation decisions for vaccination programs.